2018
DOI: 10.1111/acel.12838
|View full text |Cite
|
Sign up to set email alerts
|

Telomere dysfunction promotes transdifferentiation of human fibroblasts into myofibroblasts

Abstract: Cells that had undergone telomere dysfunction‐induced senescence secrete numerous cytokines and other molecules, collectively called the senescence‐associated secretory phenotype (SASP). Although certain SASP factors have been demonstrated to promote cellular senescence in neighboring cells in a paracrine manner, the mechanisms leading to bystander senescence and the functional significance of these effects are currently unclear. Here, we demonstrate that TGF‐β1, a component of the SASP, causes telomere dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 51 publications
1
42
0
Order By: Relevance
“…Senescent cells have been shown to induce paracrine DNA damage and senescence in healthy neighbouring cells via mechanisms involving secretion of SASP factors and increased ROS (Nelson et al , ; Acosta et al , ; Razdan et al , ). In agreement with this, our data showed that keratinocytes surrounding senescent melanocytes also exhibited significantly more telomere damage, providing evidence for a possible bystander effect of senescent melanocytes in human skin in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Senescent cells have been shown to induce paracrine DNA damage and senescence in healthy neighbouring cells via mechanisms involving secretion of SASP factors and increased ROS (Nelson et al , ; Acosta et al , ; Razdan et al , ). In agreement with this, our data showed that keratinocytes surrounding senescent melanocytes also exhibited significantly more telomere damage, providing evidence for a possible bystander effect of senescent melanocytes in human skin in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our data, previous studies have shown that stimulation of the CXCR3 receptor results in increased ROS generation (Bek et al , ). Moreover, others have also demonstrated that SASP components, notably TGF‐β1, induce paracrine telomere dysfunction in a ROS‐dependent manner (Razdan et al , ). Although the mechanisms that result in enhanced mitochondrial ROS production downstream of CXCR3 signalling have not been fully elucidated, we and others have shown that Akt phosphorylation occurs as a result of CXCR3 activation (Bonacchi et al , ; Shahabuddin et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…We observed the upregulated protein expression of TGF-β and p-Smad3 in lungs in the SiNP-treated mice (Figure 3D). So in our study, the elevated protein expression of STAT3 and IL-6 contributed to the TGF-β production which promoted the transdifferentiation from fibroblast into myofibroblast so as to accelerate the collagen production in lungs 29…”
Section: Discussionmentioning
confidence: 51%
“…During the tissue repair and wound healing, fibroblasts are promoted to transdifferentiate into myofibroblasts which are characterized by the de novo expression of αSMA and mainly in charge of production of extracellular matrix components including collagen, fibronectin, and others 29. In our study, we demonstrated that intravenous injection of SiNPs induced moderate increase of αSMA expression and collagen accumulation in lung tissues in the 45 days observation period (Figure 3A and C), indicating that SiNPs was likely to promote the transdifferentiation from fibroblast into myofibroblast thus to accelerate the production of extracellular matrix in lungs.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the other 3 groups, no obvious skin appendage regeneration was observed. (27,28). Myofibroblasts can secrete large amounts of collagen fibers (29), and the amount can reflect the condition of the granulation tissue.…”
Section: Rhfgf21-hp Enhances Granulation Formationmentioning
confidence: 99%